The Cosmos greenstone succession, Agnew-Wiluna greenstone belt, Yilgarn Craton, Western Australia: Geochemistry of an enriched Neoarchaean volcanic arc succession - de Joux, A.; Thordarson, T.; Fitton, J.G.; Hastie, A.R. (Lithos, 2014)
The geodynamic setting of the Neoarchaean Eastern Goldfields Superterrane (EGS) of the Yilgarn Craton is the subject of debate. Some authors propose plume models, while others advocate variants on a subduction accretion model for the origin of mineralised greenstone belt sequences. Felsic volcanism in the Kalgoorlie Terrane, the westernmost terrane of the EGS, is considered to have a tonalite-trondhjemite-granodiorite/dacite (TTG/D) geochemical affinity. The Cosmos greenstone succession, which lies in the Agnew-Wiluna greenstone belt (AWB) of the Kalgoorlie Terrane, contains several komatiite-hosted nickel sulphide deposits, the volcanic footwall to which consists of an intercalated succession of fragmental and coherent rocks ranging in composition from basaltic andesite to rhyolite. Light rare earth elements (LREEs) and large ion-lithophile elements (LILEs) are strongly enriched relative to high field strength elements (HFSEs) across all volcanic units, and the rocks display strong positive Pb and negative Nb anomalies. These geochemical characteristics resemble closely those of modern high-K calc-alkaline to shoshonite continental arc successions. Contrasting REE, LILE and HFSE concentrations, coupled with assimilation-fractional crystallisation (AFC) modelling, shows that the intercalated dacitic and andesitic volcanic rocks within the footwall succession are not co-genetic. Xenocrystic zircons within the felsic volcanic lithologies indicate that some assimilation of older continental crust contributed to the generation of the footwall volcanic sequence. The geochemical characteristics of the Cosmos volcanic succession indicate that parental melts were derived via partial melting of enriched peridotite that had been contaminated by subducted crustal material within the mantle wedge of a subduction zone. In contrast, two younger felsic porphyry intrusions, which cross-cut the volcanic succession, have a distinct TTG/D affinity. Therefore, these intrusions are considered to be generated via partial melting of a subducting slab and are related to local high-Ca granitoid intrusions. The Cosmos volcanic succession represents the first extrusive high-K calc-alkaline to shoshonitic volcanic arc sequence described in the Kalgoorlie Terrane and, coupled with age dating of the stratigraphy, is indicative of formation in a long-lived volcanic arc setting active from 2736Ma to later than 2724Ma. The composition and geochemical affinity of the volcanic footwall succession to the Cosmos komatiite-hosted nickel-sulphide deposits contrasts with the majority of felsic volcanic rocks within the AWB and also the wider Kalgoorlie Terrane, suggesting that the overall architecture of this region is more complex than is currently thought. Our conclusions not only have consequences for recent models of the tectonic evolution of the EGS but also contribute to the debate on the operation of plate tectonics during the late Archaean in general. The arc affinity of the Cosmos volcanic succession, containing abundant high-K calc-alkaline andesite lavas, provides further support for the operation of plate tectonics in the Neoarchaean. •We present a detailed geochemical investigation of the Cosmos greenstone succession.•The Cosmos sequence is considered to have formed in an ancient volcanic arc setting.•Volcanic lithologies have a distinct high-K calc-alkaline to shoshonite affinity.•Later intrusions have a TTG affinity and are related to regional granite intrusion.•Cosmos provides further evidence for plate tectonic operation in the Neoarchaean.